Analysis of the Implementation of Health Promotion Strategies in the Utilization of Posbindu PTM by At-Risk Groups in the UPTD Working Area of Silau Laut Health Center, Asahan Regency in 2024 - Renta, Marlina; Desideria Yosepha Ginting; Agustinus Sitepu (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
The low awareness among the community to participate in Posbindu is influenced by the lack of promotion for the Posbindu program itself. This study aims to analyze the effectiveness of health promotion strategies in increasing community participation in Posbindu PTM in the Silau Laut UPTD Health Center's working area in 2024. Using a qualitative approach with interview and observation methods, this research found that the low awareness among the community to participate in Posbindu was caused by a lack of socialization and long distances. In response, the Health Center has implemented various promotional efforts. The research results show that collaboration between the Health Center, cadres, and community leaders is crucial in increasing participation. However, more measured and sustainable strategies are needed to overcome geographical challenges. This study highlights the important role of local government in supporting the Posbindu program and provides recommendations for developing more effective health promotion programs.